Rice genetic resources in Peninsula Malaysia - Cheah, C. H.; Zainal Abidin, Mohd Idris (Malaysian Society of Applied Biology, 1979)
A survey of the literature covering the collections of rice varieties in Peninsula Malaysia was made. The resources inherent in these varieties are discussed from the point of the factors stimulating their diversity. their diversity and classification and their utilization. The present collection of local varieties stands at 1,029 listed entries representing 365 distinct varieties and these are maintained at Bumbong Lima. The conclusion drawn from this survey is that the germplasm in Peninsula Malaysia is well conserved and that if genetic erosion had taken place, it must be at the level of decreasing the diversity within a variety rather than in number of varieties. It is suggested that inheritance studies should be initiated especially in the areas of pest and disease resistance and genotype-environment interaction and that the multiline approach should beInitiatedin future breeding efforts .